Towards a rational design of solid drug nanoparticles with optimised pharmacological properties. Issue 3 (29th September 2016) - Siccardi, Marco; Martin, Phillip; Smith, Darren; Curley, Paul; McDonald, Tom; Giardiello, Marco; Liptrott, Neill; Rannard, Steve; Owen, Andrew
Abstract: Solid drug nanoparticles (SDNs) are a nanotechnology with favourable characteristics to enhance drug delivery and improve the treatment of several diseases, showing benefit for improved oral bioavailability and injectable long‐acting medicines. The physicochemical properties and composition of nanoformulations can influence the absorption, distribution, and elimination of nanoparticles; consequently, the development of nanoparticles for drug delivery should consider the potential role of nanoparticle characteristics in the definition of pharmacokinetics. The aim of this study was to investigate the pharmacological behaviour of efavirenz SDNs and the identification of optimal nanoparticle properties and composition. Seventy‐seven efavirenz SDNs were included in the analysis. Cellular accumulation was evaluated in HepG2 (hepatic) and Caco‐2 (intestinal), CEM (lymphocyte), THP1 (monocyte), and A‐THP1 (macrophage) cell lines. Apparent intestinal permeability (Papp ) was measured using a monolayer of Caco‐2 cells. The Papp values were used to evaluate the potential benefit on pharmacokinetics using a physiologically based pharmacokinetic model. The generated SDNs had an enhanced intestinal permeability and accumulation in different cell lines compared to the traditional formulation of efavirenz. Nanoparticle size and excipient choice influenced efavirenz apparent permeability and cellular accumulation, and this appeared to be cell line dependent. These findings represent a valuable platform for the design of SDNs, giving an empirical background for the selection of optimal nanoparticle characteristics and composition. Understanding how nanoparticle components and physicochemical properties influence pharmacological patterns will enable the rational design of SDNs with desirable pharmacokinetics. Abstract : Solid drug nanoparticles are a nanotechnology with favourable characteristics to enhance drug delivery, for improved oral bioavailability and injectable long‐acting medicines. The physicochemical properties and composition of nanoformulations can influence the distribution of nanoparticles and in our study nanoparticle size and excipient choice influenced apparent permeability and cellular accumulation. Our findings represent a valuable platform for the design of SDNs, giving an empirical background for the selection of nanoparticle candidates with optimal characteristics and composition.